2001
DOI: 10.1128/jvi.75.24.12098-12104.2001
|View full text |Cite
|
Sign up to set email alerts
|

Open Reading Frame III of Borna Disease Virus Encodes a Nonglycosylated Matrix Protein

Abstract: The open reading frame III of Borna disease virus (BDV) codes for a protein with a mass of 16 kDa, named p16 or BDV-M. p16 was described as an N-glycosylated protein in several previous publications and therefore was termed gp18, although the amino acid sequence of p16 does not contain any regular consensus sequence for N glycosylation. We examined glycosylation of p16 and studied its membrane topology using antisera raised against peptides, which comprise the N and the C termini. Neither an N-nor a C-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…The dominant form of BDV-M isolated from infected horses is tetrameric (15), suggesting that it is the tetramer that binds to the viral membrane, and flotation experiments have shown that BDV-M binds to membranes of BDV-infected cells (14). The interaction of the purified BDVM tetramer with brain polar lipid extract was studied by using the monolayer technique (25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominant form of BDV-M isolated from infected horses is tetrameric (15), suggesting that it is the tetramer that binds to the viral membrane, and flotation experiments have shown that BDV-M binds to membranes of BDV-infected cells (14). The interaction of the purified BDVM tetramer with brain polar lipid extract was studied by using the monolayer technique (25).…”
Section: Resultsmentioning
confidence: 99%
“…BDV-M, the M-protein of BDV, is the smallest M-protein (16.2 kDa) among all NSVs. It is located beneath the viral envelope and associates with the inner layer of the viral membrane and as such is responsible for the structural integrity and individual form of virus particles by bridging the nucleocapsid and the envelope (14). BDV-M forms oligomers both in vivo and in vitro, with tetramers as the most stable structural unit (15,16).…”
mentioning
confidence: 99%
“…The nature and strength of the membrane binding of Z were examined by various well-established membrane detachment procedures by using either sodium bicarbonate buffer at pH 10 or 2 M KCl or 50 mM EDTA before the treated samples were subjected to flotation analysis as described previously (20,21). However, none of these treatments, which characteristically remove most peripheral membrane proteins, disrupted the association of Z protein with membranes (Fig.…”
mentioning
confidence: 99%
“…BDV was originally identified as the causative agent of Borna disease, an often fatal immune-mediated neurological disease naturally occurring mainly in horses and sheep within regions of endemicity in central Europe (31). Current epidemiological data, however, indicate that the natural host range, prevalence, and geographic distribution of BDV are broader than originally thought (8,16,20,29). Experimentally, BDV has a wide host range, from birds to rodents and nonhuman primates (8,10,16,20,29).…”
mentioning
confidence: 94%
“…Experimentally, BDV has a wide host range, from birds to rodents and nonhuman primates (8,10,16,20,29). Both host and viral factors contribute to a variable period of incubation and significant heterogeneity in the symptoms and pathology associated with infection (8,10,16,20,29).BDV is an enveloped virus with a nonsegmented negativestrand RNA genome with a characteristic mononegavirales organization (4, 34, 35). However, based on its unique genetics and biological features, BDV is considered to be the prototypic member of a new virus family, Bornaviridae, within the order Mononegavirales.…”
mentioning
confidence: 99%